Biogenic Amines in Italian Pecorino Cheese - Schirone, Maria; Tofalo, Rosanna; Visciano, Pierina; Corsetti, Aldo; Suzzi, Giovanna (Frontiers in Microbiology, 2012)
The quality of distinctive artisanal cheeses is closely associated with the territory of production and its traditions. Pedoclimatic characteristics, genetic autochthonous variations and anthropic components create an environment so specific that it would be extremely difficult to reproduce elsewhere. Pecorino cheese is included in this sector of the market and is widely diffused in Italy (approximately 53.727t of production). Pecorino is a common name given to indicate Italian cheeses made exclusively from pure ewes' milk characterized by a high content of fat matter and it is mainly produced in the middle and south of Italy by traditional procedures from raw or thermized milk. The microbiota plays a major role in the development of the organoleptic characteristics of the cheese but it can also be responsible for the accumulation of undesirable substances, such as biogenic amines (BA). Several factors can contribute to the qualitative and quantitative profiles of BA’s in Pecorino cheese such as environmental hygienic conditions, pH, salt concentration, aw, fat content, pasteurization of milk, decarboxylase microorganisms, starter cultures, temperature and time of ripening, storage, part of the cheese (core, edge) and the presence of cofactor. Generally, the total content of BA’s can range from about 100-2400 mg/kg, with a prevalence of toxicologically important BA’s, tyramine and histamine. The presence of BA in Pecorino cheeses is becoming increasingly important to consumers and cheese-maker alike, due to the potential threats of toxicity to humans and consequent trade implications.